THE ROLE OF THE INTERCULTURAL INTERPRETATION OF VALUES IN LINGUISTICS - M.A. Makhkamova (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article analyzes the complexity of the process of understanding values in different cultures, in particular, it highlights how language, communication and worldviews influence the formation of these concepts. It analyzes how people from different cultural backgrounds interpret key concepts such as respect, freedom, duty and collectivism differently, which often leads to misunderstandings in intercultural communication. In order to effectively address these problems, it emphasizes the importance of building intercultural competence through cultural education, empathy and flexibility. Using the examples of Western and Eastern cultures, as well as the cultural contexts of Uzbekistan and Russia, the article demonstrates the need to develop mutual understanding through cultural awareness and ethical dialogue. In addition, the article suggests practical approaches to increasing intercultural sensitivity in academic, professional and social spheres, which will serve to form a more inclusive and respectful global dialogue.